Physiological determinants of elite mountain bike cross-country Olympic performance - Bejder, J.; Bonne, T. C.; Nyberg, M.; Sjøberg, K. A.; Baastrup Nordsborg, N. (Journal of Sports Sciences, 2019)
Detailed physiological phenotyping was hypothesized to have predictive value for Olympic distance cross-country mountain bike (XCO-MTB) performance. Additionally, mean (MPO) and peak power output (PPO) in 4 × 30 s all-out sprinting separated by 1 min was hypothesized as a simple measure with predictive value for XCO-MTB performance. Parameters indicative of body composition, cardiovascular function, power and strength were determined and related to XCO-MTB national championship performance (n = 11). Multiple linear regression demonstrated 98% of the variance (P < 0.001) in XCO-MTB performance (tXCO-MTB; [min]) is explained by maximal oxygen uptake relative to body mass (VO2peak,rel; [ml/kg/min]), 30 s all-out fatigue resistance (FI; [%]) and with a minor contribution from quadriceps femoris maximal torque (Tmax; [Nm]): tXCO-MTB = -0.217× VO2peak,rel.-0.201× FI+ 0.012× Tmax+ 85.4. Parameters with no additional predictive value included hemoglobin mass, leg peak blood flow, femoral artery diameter, knee-extensor peak workload, jump height, quadriceps femoris maximal voluntary contraction force and rate of force development. Additionally, multiple linear regression demonstrated parameters obtained from 4x30s repeated sprinting explained 88% of XCO-MTB variance (P < 0.001) with tXCO-MTB = -5.7× MPO+ 5.0× PPO+ 55.9. In conclusion, XCO-MTB performance is predictable from VO2peak,rel and 30 s all-out fatigue resistance. Additionally, power variables from a repeated sprint test provides a cost-effective way of monitoring athletes XCO-MTB performance.